Evaluating how different balancing data techniques impact on prediction of premature birth - Extended Abstract – CTDGSI 2025 - Silva, Anna Beatriz; Rocha, Elisson da Silva; Endo, Patricia Takako (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Este artigo não possui um resumo.